Effectiveness of Rastra Bulog Rice Distribution Using Agent Based Modeling and Simulation Tools - Roro Arinda Reswanti Julian Pratama; Muchammad Rusdan (Almana : Jurnal Manajemen dan Bisnis, 2021)
The Rastra Rice Program is one of the programs planned by the government to reduce the burden on target households (RTS – Rumah Tangga Sasaran). This program provides relief to the community by distributing Rastra Rice which is suitable for consumption. BULOG become one of the state-owned institutions appointed by the government to provide and distribute subsidized rice for low-income groups, the provision prioritizes the procurement of rice/rice from farmers in the country. The main objective of this research is to find a better distribution strategy so that the distribution process of Rastra rice is efficient, minimizes delays from delivery times, and minimizes the risk of storage costs. The research method used is descriptive qualitative with data collection methods using observation techniques and literature studies, while the method in determining the distribution strategy using agent-based modeling and simulation. Agent-based Model (ABM) based simulation method for Rastra rice distribution using the Multi-Agent Simulation (MASIM) stage, namely, the requirements stage, the modeling stage, the design, and architectural stage, the implementation stage, the verification stage, validation, and accreditation.